MELIHAT FILM “VINA SEBELUM 7 HARI” SEBAGAI GERAKAN ADVOKASI UNTUK KORBAN BULLYING - Dirham Asese (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
This article discusses advocacy, which is a movement to provide support for marginalized people by highlighting a case of bullying that resulted in death. Vina's case was made into a big screen film and succeeded in attracting a lot of attention from Indonesian citizens. The film "Vina Before 7 Days" tells the story of a girl who had to suffer the death of a victim of bullying which resulted in abuse. Bullying itself is widespread among teenagers by taking advantage of someone's absence which results in mental and physical harm to the victim and makes the victim ostracized in their social environment, which is why this article tries to look at the film "Vina Prior 7 Hari" as an advocacy movement. This article uses a qualitative method with a literature review to collect data and a content analysis approach to describe sources in the form of narratives or images. The form of data taken comes from films and related news media. The results of this research show the reason for making a true story into a film entitled "Vina Before 7 Days" of a murder victim, due to bullying. The making of this film provides defense and support for the victim with the aim that this case will not be forgotten and there will be no more victims of bullying. This article deliberately does not focus on advocacy for the victim's family because if defense and support is given to the victim's family then the case will lead to a system of revenge, whereas revenge is not something that advocacy wants to fight for. If you want to fight for the legal system, then advocacy is not suitable to discuss this issue because what is wrong is not the legal system but the policy makers who play with the law. So from this advocacy step, it is hoped that policy makers will pay attention to solutions so that bullying does not happen again.